FORUM EKSPERTÓWPOL-TAVI FIRST – Polish report on transcatheter aortic valve implantation (TAVI) of Edwards-Sapien prosthesis in the first 19 high risk patients with severe aortic stenosis and comorbidities - Zembala, Marian; Wilczek, Krzysztof; Przybylski, Roman; Chodór, Piotr; Nadziakiewicz, Paweł; Krasoń, Marcin; Sadowski, Jerzy; Dudek, Dariusz; Kapelak, Bogusław; Forysz, Danuta; Witkowski, Adam; Demkow, Marcin; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Patients with severe symptomatic aortic stenosis, who from November 2008 to March 2009 were treated with Edwards-Sapien transcatheter aortic valve implantation (TAVI) within the POL-TAVI First Polish Registry, were included in the analysis. Nineteen patients aged 78±4,8 years with high operation risk and Logistic EuroSCORE 25 ± 7.6% were reported (74% were females). In 15 (79%) patients the valve was implanted transapically (TA), in the other four (21%) – via the femoral arterial access (TF). The valve was successfully implanted in 16 (84%) patients, in one patient aortic valvuloplasty alone was performed. During in-hospital period two patients died (one during periprocedural period and another one – two months after the implantation). During the mean follow-up of 5 ± 1.5 months (except for one patient who is still in hospital) all patients are in NYHA class I or II. Results of the initial series of 19 TAVI patients in Poland are satisfactory, and the trial will be continued with careful medical and economical analysis.